Characterization of lower ionosphere disturbance associated with classes of solar flare using VLF monitoring system / A. Taat ...[et al.] - Taat, A.; Jusoh, M. H.; Enche Abdul Rahim, S. A.; Abdullah, M. (UiTM Press, 2018)
The response of the D-region low-latitude ionosphere has been studies for difference classes of Solar flares on October 2013 using VLF Signal from Northwest Cape, Australia (NWC, 19.8kHz) transmitter monitored at National University of Malaysia (UKM, 2.550N, 101.460E). Attention is restricted to diurnal variation and the solar x-ray effects on propagation of VLF Signal. The changes and the enhancement of amplitude signal (VLF) are related to the X-ray fluxes that measured by GOES satellite. The two main parameters of lower ionosphere which are reference height (H') and sharpness factor (β) was estimated by using the Long Wave Propagation Capability (LWPC) Code. Statistical results show both parameters is strongly depend on the flare classes and local time of flare`s occurrence. This research are also presents the trend of the amplitude perturbations correlated with the intensity of the X-ray flux by difference classes of solar x-ray flares during second peak of solar cycle 24.